Correlating XCO2 Trends over Texas, California, and Florida with Socioeconomic and Environmental Factors - Shannon Lindsey; Mahesh Bade; Yang Li (Remote Sensing, 2025)
Understanding the trends and drivers of greenhouse gases (GHGs) is vital to making effective climate mitigation strategies and benefiting human health. In this study, we investigate carbon dioxide (CO2) trends in the top three emitting states in the U.S. (i.e., Texas, California, and Florida) using column-averaged CO2 concentrations (XCO2) from the Greenhouse Gases Observing Satellite (GOSAT) from 2010 to 2022. Annual XCO2 enhancements are derived by removing regional background values (XCO2, enhancement), and their interannual changes (ΔXCO2, enhancement) are analyzed against key influencing factors, including population, gross domestic product (GDP), nonrenewable and renewable energy consumption, and normalized vegetation difference index (NDVI). Overall, interannual changes in socioeconomic factors, particularly GDP and energy consumption, are more strongly correlated with ΔXCO2, enhancement in Florida. In contrast, NDVI and state-specific environmental policies appear to play a more influential role in shaping XCO2 trends in California and Texas. These differences underscore the importance of regionally tailored approaches to emissions monitoring and mitigation. Although renewable energy use is increasing, CO2 trends remain primarily influenced by nonrenewable sources, limiting progress toward atmospheric CO2 reduction.